2011
DOI: 10.1002/prs.10505
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for identifying and mitigating thermal hazards of sustainable materials

Abstract: Sustainable materials and technologies (a.k.a. “green”) are those that are “delivered with progressively less negative impact upon the Earth.” Thermal hazards such as self‐heating, thermal runaway, fires, and explosions may be associated with a particular sustainable material or process technology. Thermal hazards are a result of the interaction between the exothermic reactivity of the material and the processing or storage conditions (e.g., environment, temperature, duration, size, and configuration). These m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Some manufacturers claim that RDF pellets can be stored for up to 3 years without significant biological or chemical degradation [5,15,18,20,24,[40][41][42][43][44][45], but the operational experience of the authors and RWE Generation shows that these claims are supposed rather than supported; hence, they can be misleading and potentially dangerous (Figure 2). To date, many studies have shown that the problems associated with RDF pellets have been due to factors such as the poor quality of the product.…”
Section: Rdf Production and Storage Hazardsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some manufacturers claim that RDF pellets can be stored for up to 3 years without significant biological or chemical degradation [5,15,18,20,24,[40][41][42][43][44][45], but the operational experience of the authors and RWE Generation shows that these claims are supposed rather than supported; hence, they can be misleading and potentially dangerous (Figure 2). To date, many studies have shown that the problems associated with RDF pellets have been due to factors such as the poor quality of the product.…”
Section: Rdf Production and Storage Hazardsmentioning
confidence: 99%
“…RDF fires are notoriously difficult to detect and extinguish when in enclosed storage spaces and can last for days or even weeks [3,7,8]. Additionally, under conducive circumstances, the effluent from RDF deep-seated smoldering fires can lead to explosions [1,2,7,[9][10][11][12][13][14][15]. Until the recent introduction of BS EN ISO 21912:2021 [10], which covers the safe handling and storage of solid recovered fuels, there was no specific guidance on fire protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation